The Effectiveness of PBL-Based HOTS in English Learning - Simanungkalit, Indra; Utanto, Yuli; Rifai RC, Achmad (Innovative Journal of Curriculum and Educational Technology, 2019)
One of the disadvantages in the process of learning that is conducted by teachers is the lack of effort to increase the effectiveness of PBL-Based High order thinking the skill of students. The purpose of this research is knowing the Learning HOTS-Based in English Learning. The research method that is used in this research is a quantitative method. The population in this study was students of class XI- Public Senior High School 12 Semarang. The sampling technique was carried out by a random sampling technique, which is class XI IPA 2 as an experimental class and XI IPA Class 1 as the control class. Learning outcomes using HOTS-based PBL-Based HOTS has increased pre-test and post-test values from 33.47 to 35.00 while the Discovery Learning-based HOTS has increased from 33.29 to 34.20, (2) on the PBL-Based HOTS, pre-test value of high motivated-students is 31.89 has increased in post-test of 6.55 to 38.44. While the low-motivated students have a pre-test value of 29.89 and have increased in post-test of 1.89 to 31.78 for Discovery Learning-based HOTS, pre-test value on high-motivated students of 34.11, it has increased in post-test of 0.45 to 34.56 while in low-motivated students has the pre-test value of 29.67, experiencing an increase on post-test of 3.11 to 32.78, and (3) there is interaction between PBL-based HOTS with Discovery Learning-Based HOTS to student learning outcomes. The research is capable of generating synthesis about the effectiveness of Discovery Learning-Based HOTS in English learning, providing empirical evidence so that schools and teachers can select effective learning models and it can be a basis or a reference to further research in English learning.